Bridging Disciplines: Inter–Multi–Transdisciplinary Pathways for Sustainable Urban Development in the Western Balkans - Milošević, Dragan (Geographica Pannonica, 2026)
Western Balkan cities currently stand at a critical inflection point, characterized by the convergence of intensifying climate and hydrometeorological hazards, acute environmental pollution, and profound demographic imbalances. This article argues that the region’s persistent implementation gap—frequently described as being "full of plans but short of traction"—is not primarily a technological deficiency but a structural crisis of knowledge integration and governance. By analyzing the compounding nature of risks, where environmental stressors cascade across interdependent infrastructure systems, the study demonstrates that traditional, siloed policy responses are insufficient. Instead, it posits that achieving urban resilience requires a fundamental shift from technocratic management to inter-, multi-, and transdisciplinary frameworks. Four practical pathways are proposed to operationalize this shift: (1) embedding environmental and social risk assessment into the core of sustainable urban development; (2) integrating service delivery to simultaneously support livelihoods and sustainability; (3) establishing ’frugal’ urban observatories that bridge official monitoring gaps with citizen science, providing a resource-efficient counterpart to expensive ’smart city’ architectures; and (4) institutionalizing co-production to ground policy in local realities. Ultimately, the paper suggests that by treating integration as a delivery mechanism rather than an academic ideal, Western Balkan cities can transform into "integration laboratories," demonstrating how to govern sustainability transitions effectively under strict fiscal and administrative constraints.